Feasibility Study to Evaluate the Proportion of Cancer Attributable to Modifiable Factors of Risk in Peru and Latin America: Estudio de Factibilidad para Evaluar la Proporción de Cáncer Atribuible a Factores de Riesgo Modificables en el Perú y Latinoamérica - De La Cruz Vargas, Jhony A. (2020)
Objective: To evaluate the feasibility of the methodological proposal to estimate the incidence and mortality due to cancer attributable to modifiable risk factors for Peru and Latin America. Methods: Pilot study, ecological from secondary sources. Modifiable risk factors, exposure prevalence, relative risks of these factors (RR) or an approximation by means of possibilities ratio (OR) were searched and selected. The information was recorded in a data collection form which was validated by expert judgment. For the calculation of the Population Attributable Fraction (FAP), the formula proposed by Parkin was tested and a statistical simulation model was developed with R. Studio V. 3.6.1 software. Results: In Peru there are prevalence studies for the majority of modifiable risk factors; Likewise, studies with OR estimates for several of the factors are available in Latin America; however, studies from the United States had to be used for the remaining factors. No national studies of ionizing or ultraviolet radiation were found. The syntax of the statistical simulation model was tested, which proved to be valid and consistent with the results of international FAP studies within the ranges of published studies. Conclusion: It is feasible and viable to carry out PAF studies of modifiable risk factors for cancer in Latin American countries, particularly in Peru, where the information required for its estimation is available.